Sifat Fisik Pati Ganyong (Canna edulis Kerr.) Termodifikasi dan Penambahan Gum Xanthan untuk Rerotian (Physical Characteristics of Modified Canna edulis Kerr. Starch and Gum Xanthan for Bakeries) - Parwiyanti Parwiyanti; Filli Pratama; Agus Wijaya; Nura Malahayati; Eka Lidiasari (Agritech, 2016)
Modification of Canna starch through heat-moisture treatment (HMT) and gum xanthan (GX) treatment was conducted to improve the disadvantage of natural Canna starch in order to expand its usage in food industry, especially for bakery products. The research was arranged in a factorial randomized complete block design with three factors (temperature, incubation time, and GX concentrations) and three replications for each factor.  The modified Canna  starch by HMT possessed water content of 15 % as well as combination of temperature (80 °C and 100 °C), periods (8 and 16 hours) and concentration of GX (0; 0.5; 1; 1.5 and 2 %). The observed variables were the swelling power, water solubility index, water absorption index, baking expantion, and bulk density of modified Canna starch. The result showed that the modification of Canna starch by temperature, time of HMT and concentration GX produced modified starch with physical properties that significantly differ among treatments and natural starch.  Modified Canna starch by treatments of 80 °C, 8 hours, and 1 % xanthan gum concentration showed had swelling power 16.90 ± 0.48 g/g, water solubility index 10.28 ± 0.25 %, water absorption index 112.58 ± 0.38 %, baking expantion 0.94 ± 0.11 mL/g and bulk density 0.73 ± 0.026 g/mL which alike with wheat flour so that it can be further developed as wheat flour substitute on bakery products.